Aplikasi Logika Fuzzy Untuk Prediksi Kejadian Hujan (Studi Kasus : Sub das Siak Hulu) - Hafidzilhaj Harys; Imam Suprayogi; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Most important information regarding of weather especially the rain is very useful for human routines. At this writing used fuzzy logic which aims to made a approaching prediction of raining on Sub DAS Siak Hulu. The Data that used is the rainfall data and climatological data from 2010 through 2012 with a prediction that will be done for the year 2011. The rainfall data is been taken from Pasar Kampar station which sourced from Balai Wilayah Sungai III and then for climatology data took from Pasar Kampar station and from website www.wunderground.com. For the input of rain prediction model used 6 variables that is air temperature, relative humidity, wind speed, barometric pressure, total layers of clouds, and the sun shines with long output variable is rainfall. For the measurement of the accuracy of prediction Mean Square Error formulation used. Based on the results of the verification of the prediction of rainfall had a median value of ratanya was 66% and for the results of the verification of average rain events is 65%. Key words: rainfall, weather, prediction, fuzzy inference system